A Complex Inoculant of N2-Fixing, P- and K-Solubilizing Bacteria from a Purple Soil Improves the Growth of Kiwifruit (Actinidia chinensis) Plantlets - Shen, Hong; He, Xinhua; Liu, Yiqing; Chen, Yi; Tang, Jianming; Guo, Tao (Frontiers in Microbiology, 2016)
Limited information is available if the application of plant growth promoting bacteria (PGPB) can promote soil nutrient availability and plant growth, especially for fruit crops. This study evaluated PGPB, isolated from a vegetable purple soil in Chongqing, China, to increase soil nitrogen (N), phosphorus (P) and potassium (K) availability; as well as the growth of kiwifruit (Actinidia chinensis). Three out of 17 bacterial isolates with a high capacity for N2-fixation and P- and K-solubilization were identified by phenotypic and 16S rRNA sequencing. The three isolates were identified as Bacillus amyloliquefaciens (XD-N-3), B. pumilus (XD-P-1) and B. circulans (XD-K-2) and then mixed as a complex bacterial inoculant. Four treatments of (1) no-fertilizer and no-bacterial inoculant (Control), (2) no-bacterial inoculant and a full-rate of chemical NPK fertilizer (CF), (3) the complex inoculant (CI), and (4) a half-rate CF and full CI (1/2CF+CI), a pot experiment then evaluated effects of this complex inoculant on soil microflora, kiwifruit growth, soil N2-fixation, and P- and K-solubility. Results indicated that the growth of N2-fixing, P- and K-solubilizing bacteria was ranked from greatest to least as 1/2CF+CI ≈ CI > CF ≈ Control. Though generally without significant treatment differences in soil total N, P or K, significantly greater soil available N, P or K was respectively patterned as 1/2CF+CI ≈ CI > CF ≈ Control, as 1/2CF+CI > CF > CI > Control or as 1/2CF+CI > CF ≈ CI > Control, indicating an improvement of soil fertility through the complex inoculant. In regards to plant growth, greater total plant biomass and total N, P and K accumulation among treatments were ranked as 1/2CF+CI ≈ CI > CF > Control. Additionally, the level of leaf PPO (polyphenol oxidase) activity ranked as CF > 1/2CF+CI ≈ Control ≈ CI, while MDA (malondialdehyde) contents as Control > CI ≈ CF > 1/2CF+CI. In short, the complex inoculant was able to improve available soil N, P and K and kiwifruit growth (CI vs. Control). These results promote a better understanding of the potential of using a complex bacterial inoculant for promoting soil fertility and plant growth.